PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR BERBASIS AUGMENTED REALITY MATERI FABEL SISWA KELAS 2 - Nurhidayah, Fatma; Amalia, Shofi Nur; Wafa, Khoirul (Universitas Negeri Medan, 2024)
The research aims to develop an augmented reality-based comic book environment to improve literacy in elementary school students. This research used the ADDIE development model and was conducted on 22 grade 2 students at SDN Sumberingin 04. Data collection techniques used include observation, questionnaires and documentation. Data analysis includes analysis of validity, effectiveness and media attractiveness. The validation results illustrate that the augmented reality-based picture storybook media is very valid, with a percentage of 89.5% for media expert validation, 91% for material expert validation, and 90% for language expert validation. In the effectiveness test, the teacher's response showed a percentage of 100%, which means it was very effective. Meanwhile, the attractiveness test through student responses also showed a percentage of 100%, which is included in the very attractive category. The reliability of student responses was calculated using SPSS with a Cronbach alpha value of 0.773. Based on the results of the analysis, it can be concluded that the augmented reality-based picture story book media developed is suitable for use as a learning medium to increase the desire for reading literacy in elementary school students. It is hoped that this media development will be able to provide positive assistance in efforts to improve the quality of learning and students' literacy skills.